Impact of Entrepreneurial Infrastructure on Profitability of Hotels in Minna, Nigeria. - Baba Isah Usman; Umaru Mustapha Zubairu; Daniel Anyebe; Dauda Abdulwaheed; Isaiah Adeleke; Ekanem Ediuku (LPPM of NAROTAMA UNIVERSITY, 2022)
Purpose: This study aims to examine the impact of Entrepreneurial Infrastructure (EI) on profitability of Small and Medium Enterprises (SMEs), focusing on hotels in Minna, Nigeria. Methodology: Sequential Explanatory Mixed research method was adopted. Purposive Sampling Technique was used to obtain a sample size of 51 out of a population of 70 hotels in Minna for collection of quantitative data via questionnaires, while Simple Random Sampling Technique was used to select 10 interviewees for collection of qualitative data via interviews. Descriptive statistics was employed in analysing the quantitative data, while thematic analysis was used in analysing the qualitative data. Findings: Quantitative findings revealed that the available EI in Minna had a negative impact on the profitability of hotels, while qualitative findings also revealed that interviewees generally felt a poor impact of EI on the profitability of their hotels. Practical implications: These findings would be useful to potential and practicing entrepreneurs in the hotel industry, policy makers and the academic community. It is recommended that government at all levels should formulate policies that will address challenges of the deplorable condition of EI in Nigeria. Paper type: Research paper